Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.22367/jem.2021.43.18
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the IFRS 15 implementation on the revenue based earnings management in Poland

Abstract: Aim/purpose – This paper aims at investigating whether the International Financial Reporting Standard (IFRS) 15 Revenue from Contracts with Customers implementation in Poland has affected earnings management that uses discretion in revenue recognition to avoid losses and earnings decreases. Design/methodology/approach – The empirical studies were conducted using a sample of 80 entities from four industries listed on the Warsaw Stock Exchange (WSE) in Poland from 2016 to 2019. Cay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 30 publications
2
8
0
6
Order By: Relevance
“…Porém, nessa pesquisa constatou-se que o novo padrão não influenciou significativamente a prática discricionária de gerenciamento de resultado nas empresas da B3, em contraponto ao estudo de Braga (2020), que fez uma análise da prática de gerenciamento de receitas a partir de outros setores, períodos e empresas nacionais e internacionais. Braga (2020) foi de encontro aos achados de Morawska (2021) que não identificou impacto da IFRS 15 nos níveis de gerenciamento de receitas nas empresas da Polônia.…”
Section: Tabelaunclassified
See 1 more Smart Citation
“…Porém, nessa pesquisa constatou-se que o novo padrão não influenciou significativamente a prática discricionária de gerenciamento de resultado nas empresas da B3, em contraponto ao estudo de Braga (2020), que fez uma análise da prática de gerenciamento de receitas a partir de outros setores, períodos e empresas nacionais e internacionais. Braga (2020) foi de encontro aos achados de Morawska (2021) que não identificou impacto da IFRS 15 nos níveis de gerenciamento de receitas nas empresas da Polônia.…”
Section: Tabelaunclassified
“…Há na literatura estudos brasileiros e de outros países que destacam os efeitos da aplicação da nova norma com recomendações sobre as políticas contábeis (Dalkilic, 2014), na análise de efeitos indiretos (Rutledge, Karin & Kim, 2016), na relevância com adoção antecipada (Dani, Santos, Panucci, Filho & Klann, 2017;Trabelsi, 2018), no value relevance (Altaji & Alokdeh, 2019;Braga, Santos & Nascimento, 2022;Onie, Ma, Spiropoulos & Wells, 2022), no gerenciamento de resultados (Tutino, Regoliosi, Mattei, Paoloni & Pompili, 2019), e no gerenciamento de receitas (Braga, 2020;Morawska, 2021).…”
Section: Introductionunclassified
“…However, this research found that the new standard did not significantly influence the discretionary practice of results management in B3 companies, against to the study by Braga (2020), which made an analysis of the practice of revenue management from other sectors, periods, and national and international companies. Braga (2020) foi de encontro aos achados de Morawska (2021) que não identificou impacto da IFRS 15 nos níveis de gerenciamento de receitas nas empresas da Polônia. Braga (2020) was in line with the findings of Morawska (2021) who did not identify the impact of IFRS 15 on revenue management levels in Polish companies.…”
Section: Tablementioning
confidence: 99%
“…There are studies in the Brazilian literature and in other countries that highlight the effects of applying the new standard with recommendations on accounting policies (Dalkilic, 2014), in the analysis of indirect effects (Rutledge, Karin & Kim, 2016), in the relevance of early adoption (Dani, Santos, Panucci, Filho & Klann, 2017;Trabelsi, 2018), in the value relevance (Altaji & Alokdeh, 2019;Braga, Santos & Nascimento, 2022;Onie, Ma, Spiropoulos & Wells, 2022), in the earnings management (Tutino, Regoliosi, Mattei, Paoloni & Pompili, 2019), and revenue management (Braga, 2020;Morawska, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have analyzed the effects of IFRS 15 on earnings quality include that of Tutino et al (2019) in a sample of Italian companies and the study by Morawska (2021) in Polish companies. Both studies find evidence that the standard allows for greater EM in both samples analyzed.…”
Section: Introductionmentioning
confidence: 99%